2017
DOI: 10.1128/aac.00111-17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Investigational Antifungal VT-1161 in Treating Naturally Occurring Coccidioidomycosis in Dogs

Abstract: Coccidioidomycosis can be a chronic, systemic fungal infection requiring long-term to lifetime medication. Thus, there is a need for improved antifungal agents with greater efficacy and reduced toxicity. VT-1161 has a low affinity for mammalian cytochromes and potently inhibits fungal CYP51 with proven efficacy in murine models of central nervous system (CNS) and respiratory coccidioidomycosis. Dogs experience coccidioidomycosis similar to humans and are a useful preclinical model for naturally occurring disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The structurally related compounds VT-1161 and VT-1129 have been proposed as antifungal agents that effectively target the LDMs of several fungal pathogens, ranging from Ascomycetes and Basidiomycetes to Zygomycetes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These drugs use the weaker affinity for the heme iron conferred by a tetrazole instead of a triazole, together with additional contacts within the LBP, to bind preferentially with their fungal target and minimize interaction with human cytochrome P450s (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)40). We have used a yeast expression system and clinical isolates of the fungal pathogens C. albicans and C. glabrata to demonstrate that the efficacy of this new class of azole drugs can be compromised by mechanisms of antifungal resistance common in these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The structurally related compounds VT-1161 and VT-1129 have been proposed as antifungal agents that effectively target the LDMs of several fungal pathogens, ranging from Ascomycetes and Basidiomycetes to Zygomycetes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These drugs use the weaker affinity for the heme iron conferred by a tetrazole instead of a triazole, together with additional contacts within the LBP, to bind preferentially with their fungal target and minimize interaction with human cytochrome P450s (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)40). We have used a yeast expression system and clinical isolates of the fungal pathogens C. albicans and C. glabrata to demonstrate that the efficacy of this new class of azole drugs can be compromised by mechanisms of antifungal resistance common in these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…6 The development of a new class of antifungals that targets fungal CYP51 without significantly affecting the human homologue 6 shows promise for improved treatment options. One of these compounds, VT-1161, showed great preclinical promise in treating a wide range of mycoses, including fluconazole-susceptible and -resistant strains of Candida albicans in vulvovaginal candidiasis, dermatophytosis, mucormycosis and coccidioidomycosis, [7][8][9][10][11] and is currently in Phase 2 clinical trials for the treatment of vulvovaginal candidiasis and onychomycosis. Another associated compound, VT-1129, has shown great preclinical efficacy in treatment of cryptococcosis.…”
Section: Introductionmentioning
confidence: 99%
“…Another associated compound, VT-1129, has shown great preclinical efficacy in treatment of cryptococcosis. 12 The compounds' efficacy against azole-resistant Candida strains, 7,13 the low potential for drug-drug interactions 6 and their long half-lives 7,8,11 make them attractive options for patients with PIDDs that manifest with CMC. In this study, we examined whether J Antimicrob Chemother 2018; 73: 151-155 doi:10.1093/jac/dkx352 Advance Access publication 10 October 2017 VT-1129 and VT-1161 were effective in vitro and in vivo against fluconazole-susceptible and -resistant strains of Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…Animal model studies have shown that VT1161 can be used to prevent or treat mucormycosis caused by Rhizopus arrhizus , and can also be used for treatment of mouse modeling infection or canine naturally occurring coccidioidomycosis (Shubitz et al, 2015, 2017; Gebremariam et al, 2017). In addition, in a mouse model, VT1611 can treat oropharynx or vaginal Candidiasis caused by fluconazole sensitive or resistant C. albicans (Break et al, 2018b).…”
Section: Traditional and Novel Cyp51-targeting Antifungal Agentsmentioning
confidence: 99%